Cooperativas de trabalho de professores no ensino superior privado na cidade de São Paulo. Uma forma de precarização o trabalho docente (1994 - 2005) - Oliveira, Sergio Macedo (2008)
With the crisis of the Social Welfare State, and the advent of neoliberal policies in 1990, many changes occurred in the labor world. Privatization, free competition, free enterprise and a market economy were the agents of "new" economic and social vision. In the labor world, the consequences were the employment instability, the reduction of sectors and intensification of activities, the outsourcing of production and services. It was the same in Higher Education, with the expansion of the private sector, in which the educational institutions are inclined to profit, the pressure of competition prompted resulted in the adoption of different forms of labor activity, the cooperative work of teachers among them. Founded and organized by maintainers of the private education network, the labor teachers´ cooperatives, in higher education, were created with the clear objective of maintaining and expanding profit margins. Our focus is resumed to higher education, which seek to analyze the teachers´ labor cooperatives. The precariousness of such work was shown in intensification, reduction costs and wages, loss of previous labor rights, including the demoralization of the profession, all this has been registered in our field research. The result of all these changes has been directed at teachers, who were found in a precarious way of being and work.